Human Long Noncoding RNA Regulation of Stem Cell Potency and Differentiation - Seahyoung Lee; Hyang-Hee Seo; Chang Youn Lee; Jiyun Lee; Sunhye Shin; Sang Woo Kim; Soyeon Lim; Ki-Chul Hwang (Stem Cells International)
Because of their capability of differentiation into lineage-specific cells, stem cells are an attractive therapeutic modality in regenerative medicine. To develop an effective stem cell-based therapeutic strategy with predictable results, deeper understanding of the underlying molecular mechanisms of stem cell differentiation and/or pluripotency maintenance is required. Thus, reviewing the key factors involved in the transcriptional and epigenetic regulation of stem cell differentiation and maintenance is important. Accumulating data indicate that long noncoding RNAs (lncRNAs) mediate numerous biological processes, including stem cell differentiation and maintenance. Here, we review recent findings on the human lncRNA regulation of stem cell potency and differentiation. Although the clinical implication of these lncRNAs is only beginning to be elucidated, it is anticipated that lncRNAs will become important therapeutic targets in the near future.